REVIEW: GERMINAL CELL APOPTOSIS BY HERBAL MEDICINE - Situmorang, Putri Cahaya; Ilyas, Syafruddin (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Apoptosis is a mechanism of cell death with a main role in cell recycling, which occurs in several organs: Testical, placenta, prostate, breast, ovarian, and cancer cells. Apoptotic signal pathway may be used to repair reproductive health disorders. Signal pathway of germ cell usually begins with extrinsic apoptotic pathway involving Fas/FasL molecule and mitochondrial pathway with Bcl-2 protein component. Apoptotic process in germ cell can also be triggered by exposing certain plant secondary metabolite to certain cells. Many plants have been reported successfully triggering apoptotic properties, i.e. (1) Areca catechu, (2) Carica papaya, (3) Camellia sinensis, (4) Curcuma domestica, (5) Costus speciosus, (6) Gossypium hirsutum, (7) Hibiscus spp., (8) Luffa aegyptiaca, (9) Momordica charantia, (10) Nicotiana tabacum, (11) Olea europaea, (12) Ocimum basilicum, and (13) Zingiber officinale. The metabolites may induce apoptosis through upregulating Fas/Fas-L and p53 expression, Bax/Bcl-2, along with caspase-3 activation. The mentioned plants then will induce apoptosis in germ cell and may become promising candidates to treat cancer as evidenced from extensive laboratory studies.